BLACK SEA RAPANA VENOSA - A PROMISING SOURCE OF ESSENTIAL LIPIDS - Veselina Panayotova; Albena Merzdhanova; Diana A. Dobreva; Rositsa Stancheva (Peytchinski Publishing, 2019)
Background: A diet rich in seafood has been linked to a variety of health benefits. While worldwide overfishing results in declining fish stocks, the growing demand for alternative sources of marine lipids has been expected. Rapana venosa (veined Rapa whelk) has become valuable seafood with nutritional and economic importance in the Black Sea region. Purpose: The aim of the present study was to provide knowledge about biologically active lipids in Black Sea Rapana venosa, harvested in the region of Varna. Material/Methods: Lipid classes were separated and purified by column and thin-layer chromatography. The saponifiable lipid fraction was derivatized into fatty acid methyl esters (FAMEs) and analysed by gas chromatography-mass spectrometry (GC-MS). Non-saponifiable lipids were identified by high pressure liquid chromatography coupled with UV/Vis and fluorescence detectors (HPLC-UV-FL). Results: Rapana venosa was characterized by low lipid content (0.50 g.100g-1 ww) with beneficial PUFA/SFA and n-6/n-3 ratios and high content of vitamin D3 and astaxanthin. Lipids comprised mainly of polar lipids. Polyunsaturated fatty acids represented more than 50% of total fatty acids, most abundant being from the omega-3 series. Sum of EPA and DHA accounted at 40.8% of total fatty acids. Lipid quality indices indicated the good anti-atherogenic and atni-trombogenic properties (AI and TI < 1) of rapana meat. Conclusions: The study revealed that Rapana venosa from the Black Sea is a good source of high quality marine lipids and presents а high potential for developing functional foods and/or dietary supplements with beneficial health effects.